Trade and economic relations between Russia and the Horn of Africa countries as part of expanding the geography of cooperation: the food security - Artem S. Vasilev (RUDN Journal of Economics)
The relevance of the topic under study is explained by the fact that in conditions of fragmentation of the global economy, global mechanisms for ensuring food security stop working. Despite long-term attempts to eradicate hunger and malnutrition, including global initiatives within the framework of achieving the second Sustainable Development Goal, in recent years, especially after the coronavirus pandemic and geopolitical changes, there is an increase in the importance of subregional and regional efforts to address food security issues, including the development of international economic cooperation and the conclusion of new trade agreements. Under these conditions, Russian-African political, trade and economic relations began to develop actively, including relations with the countries of the Horn of Africa, one of the regions of the world most susceptible to hunger. The purpose of the study is to determine the nature of trade and economic relations between the Russian Federation and the countries of the Horn of Africa. The research is based on the analysis of data presented in academic literature, the analysis of available and relevant statistical information, the analysis of data from international and domestic organizations and the analysis of expert information. It is revealed that in the countries of the Horn of Africa, food security is characterized by a high degree of vulnerability due to both natural climatic conditions and socio-economic factors; at the same time, differentiation of the characteristics of the food situation is observed between these countries. The expediency of developing the economic interests of the Russian Federation in the Horn of Africa through the realization of its resource potential in the field of food security is substantiated. The Russian Federation has significant opportunities for supplying food and agricultural technologies, which can contribute to strengthening food security in these countries and at the same time expand trade and economic cooperation. It is revealed that trade and economic relations between Russia and the countries of the Horn of Africa are characterized by significant potential for growth: against the background of increasing interest in strengthening ties in the field of food security, the Russian Federation seeks to develop direct and long-term relations with African partners. Promising areas of trade and economic cooperation between the Russian Federation and the Horn of Africa countries are identified, which include the following aspects: general security of the Horn of Africa; export of agro-industrial products; exchange of experience and contributing to digitalization of agricultural sector; optimization of supply chains; development of infrastructure for food storage locally.